2014
DOI: 10.1002/btpr.1968
|View full text |Cite
|
Sign up to set email alerts
|

Cell culture media supplementation of uncommonly used sugars sucrose and tagatose for the targeted shifting of protein glycosylation profiles of recombinant protein therapeutics

Abstract: Protein glycosylation is an important post-translational modification toward the structure and function of recombinant therapeutics. The addition of oligosaccharides to recombinant proteins has been shown to greatly influence the overall physiochemical attributes of many proteins. It is for this reason that protein glycosylation is monitored by the developer of a recombinant protein therapeutic, and why protein glycosylation is typically considered a critical quality attribute. In this work, we highlight a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Finally, numerous previous studies have demonstrated the impact of media on glycosylation (Brühlman et al, 2015; Hossler et al, 2014; Surve and Gadgil, 2015). Thus, it will be of great value to integrate our model with models of other metabolic pathways.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, numerous previous studies have demonstrated the impact of media on glycosylation (Brühlman et al, 2015; Hossler et al, 2014; Surve and Gadgil, 2015). Thus, it will be of great value to integrate our model with models of other metabolic pathways.…”
Section: Discussionmentioning
confidence: 92%
“…From CHO cell line 1, mAb-1 samples were generated through cell culture media supplementation of D-arabinose, sucrose, as well as a glucose-only experimental control condition. Sucrose (70 mM) was supplemented into both the basal and feed medias to facilitate production of large quantities of high mannose N-glycans, 17 to contrast with the reduced levels of high mannose N-glycans facilitated through the use of D-arabinose. A summary of the N-glycoform profile for mAb-1 generated for the purposes of this testing is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…A change in pH from 6.9 to 7.4 was shown to influence the specific growth and mAb production rates as well as the glycosylation profile of IgG3 produced in hybridoma cells (Müthing et al, 2003). Finally, a multitude of chemical supplements added in either media or feeds have been described in the literature as effective glycosylation modulators and are summarized in detail in Table 1 (Bischoff, Liscum, & Kornfeld, 1986;Bruhlmann et al, 2017;Chang et al, 2007;Chen & Harcum, 2006;Crowell, Grampp, Rogers, Miller, & Scheinman, 2007;Foddy & Hughes, 1988;Gramer et al, 2011;Gramer, Goochee, Chock, Brousseau, & Sliwkowski, 1995;Green, Adelt, Baenziger, Wilson, & Van Halbeek, 1988; Gross et al, 1986;Gu & Wang, 1998;Hollister, Conradt, & Jarvis, 2003;Hossler et al, 2014;Jing, Qian, & Li, 2010;Jones et al, 2004;Kamińska, Dzięciol, & Kościelak, 1999;Keppler, Horstkorte, Pawlita, Schmidt, & Reutter, 2001;Kuntz, Zhong, Guo, Rose, & Boons, 2009;Li, 2014;McCracken, Kowle, & Ouyang, 2014;Mitchelson, Hughes, Mondia, & Hyde-Deruyscher, (2015); Pande, Rahardjo, Livingston, & Mujacic, 2015;Rillahan et al, 2012;Rodriguez, Spearman, Huzel, & Butler, 2005;Slade, Caspary, Nargund, & Huang, 2016;Tropea et al, 1990;Yin et al, 2017;Zhang et al, 2016). Sou et al evaluated the influence of a temperature shift from 36.5 to 32°C in the late exponential phase of a fed-batch experiment on the mAb Fc-glycan profile.…”
mentioning
confidence: 99%